Allogeneic transplantation for chronic lymphocytic leukemia in the age of novel treatment strategies - Schwarzbich, Mark-Alexander; McClanahan, Fabienne; Gribben, John G. (Oncology, 2016)
Hematopoietic stem cell transplantation (HSCT) is the only established potentially curative treatment option for chronic lymphocytic leukemia (CLL) to date. However, this approach is associated with high toxicity and significant treatment-related morbidity and mortality; thus, it is suitable for only a minority of high-risk patients, given that most persons with CLL have comorbidities and are of advanced age. Until very recently, international guidelines recommended HSCT for physically fit patients who displayed poor-risk features or had only a short response to immunochemotherapy. In the wake of novel treatment approaches that offer high efficacy and highly durable responses with little toxicity, our approach to HSCT in CLL needs to be re-evaluated. While we wait for data on the long-term efficacy of novel therapies to inform the choice of HSCT or alternative treatment, strategies must be assessed individually for every patient, and treatment must be conducted in the setting of randomized clinical trials whenever possible.
Gesehen am 08.08.2019